Teachers' implementation of the standard-based English language curriculum in year 1 basic literacy instruction in selected schools in Pahang, Malaysia - Sulaiman, Suriati (2016)
The standard-based English language curriculum was fairly new in Malaysian primary schools. Thus, this study investigated teachers‟ implementation of the new language curriculum in Year 1 basic literacy instruction in selected schools in Pahang. The study described what the participants perceived about: (1) the new curriculum, particularly the standard-based English language curriculum, phonics approach and teacher professional knowledge; (2) needs; (3) concerns; and (4) challenges that they encountered, and how they actually implemented: (1) lesson planning and preparation of basic literacy instruction; (2) basic literacy instruction; and (3) assessment of pupils‟ learning progress in basic literacy skills. A multiplecase study was carried out that involved five teachers from five national primary schools to explore these issues through seven research questions and data were analysed from classroom observations, semi-structured interviews, and corresponding documents. The research findings suggested that the participants had positive perceptions of the SBELC, phonics approach, and their professional knowledge despite their needs for instructional materials, instructional technology, and professional development trainings. The findings also revealed that the expert and proficient participants expressed their concerns for pupils‟ learning, the competent and advanced beginner participants were more likely to have concerns about teaching, while concerns for self were identified in the novice participant. As they implemented the curriculum, the participants encountered some challenges in relation to teaching strategies, activities, instructional materials, mixed-ability groups of pupils, and school textbook. The instructions were planned and prepared in the short term and as such the participants were still at the LoU III of Mechanical Use level. Yet, the lesson plans complied with the curriculum standards and conformed to the district standard format. The participants‟ instructions aligned directly with the determined learning standards. The participants used numerous teaching strategies and corresponding instructional materials for which they received positive feedback from the pupils. To assess the pupils‟ learning progress in basic literacy skills, the participants carried out three types of classroom assessments, namely activity-based, reading, and written assessments continuously and in informal way while the teaching and learning sessions were still going on. Multiple types of assessment instruments were designed according to the types of assessments and often, the instruments were adapted from various sources, but one participant sometimes self-designed the instruments. Based on the findings, some changes were proposed to improve basic literacy instruction in lower primary schools. This study provided awareness of Year 1 teachers‟ perceptions of the new language curriculum, needs, concerns, and some challenges that they faced in respond to curriculum change and implementation which would help the Ministry of Education, as the sponsor of my study to gauge teacher‟s perceptions of the new language curriculum and later gives each individual teacher necessary support to ensure success of its implementation. The findings also provided scientific evidence of the current and quality of curriculum implementation that educational leaders could use to drive decisions and actions before they launch the revised SBELC in 2017.